Competency-Based School Curriculum: A Development and Implementation Framework - Thummaphan, Phonraphee; Sripa, Kantita; Prakobthong, Watcharanon (Community and Social Development Journal, 2022)
Competency-based school curriculum development is a key mechanism for successful implementation of the national curriculum framework. However, the problem discovered is that schools continue to lack knowledge and clear guidelines, so the purpose of this study is to prepare the development process framework for competency-based school curriculum of pilot schools in the education sandbox. This study employs an explanatory sequential design mixed-method research methodology, beginning with quantitative research using online questionnaires to survey opinions from 224 pilot schools in six areas of the education sandbox, then moving on to a qualitative multi-case study using focus group discussions with administrators and teachers from 18 schools in six areas, and finally a connoisseurship of 15 experts. According to the findings, the main idea behind the development process framework for competency-based school curriculum is to focus on success in developing learners' learning competencies related to work and life. The curriculum development process includes the following components: 1) competency-based curriculum design focuses on determining core competencies and developing appropriate learning designs; 2) learning management that focuses on competency development and learning assessment that emphasizes individual progress; and 3) competency-based curriculum management, which includes appropriate study time structure, adequate preparation for action, and evaluation for continuous improvement. These findings are critical for implementing the national curriculum framework effectively.